LINGUOPRAGMATIC AND LINGUOCULTURAL STUDY OF NON-LITERARY LEXICON IN ENGLISH AND UZBEK LANGUAGES - Xolmatova Ergashoy, (Research Focus International Scientific Journal, 2022)
Today, in linguistics, much attention is paid to the difference between Uzbek and English lexicon. The comparative research method is becoming especially important. In this article, we will give general information about linguopragmatic and linguocultural study of non-literary lexicon in english and uzbek languages.